Timing Synchronization for Mc-Cdma Systems Using a Time-Multiplexed Synchronization Channel - Pham Hong Ky; Nguyen Duc Long (Universitas Gadjah Mada, 2006)
In this paper, we present a synchronization algorithm for Multi-Carrier CDMA (MC-CDMA) systems using a time-multiplexed synchronization channel. The simulations results show that a system using proposed algorithm has much higher timing detection probability than using other algorithms, especially in exponential decay multipath fading.